Hierarchical ordered macroporous/ultrathin mesoporous carbon architecture: A promising cathode scaffold with excellent rate performance for rechargeable Li-O2 batteries. (July 2017) - Yang, Wencun; Qian, Zhengyi; Du, Chunyu; Hua, Chao; Zuo, Pengjian; Cheng, Xinqun; Ma, Yulin; Yin, Geping
Abstract: In spite of the ultrahigh theoretical energy density, non-aqueous Li-O2 batteries are still constrained by their inefficient cathodes. Here, we report the synthesis of a distinctive hierarchical carbon architecture (HOM-AMUW) for Li-O2 batteries, which consists of highly ordered macropores (250 nm) with abundant mesopores on their ultrathin walls (4–5 nm). This carbon architecture exhibits unprecedented discharge capacity of 37523 mAh g −1 and 12686 mAh g −1 at the current density of 500 mA g −1 and even 2000 mA g −1, respectively. After further functionalization by low crystalline Ru nanoclusters, the resulted Ru-HOM-AMUW architecture presents a much low charge polarization and outstanding cycling stability. The significant performance enhancement is mainly attributed to the unique hierarchical porous structure, wherein the ordered macropores and ultrathin mesoporous walls remarkably enhance the access capability of O2 or Li + to the numerous active sites, and the large pore volume easily accommodates the discharge products. Moreover, the hierarchical porous structure modulates the morphology of discharge products to three-dimensional porous structure with high charge transport, which also contributes to the striking rate capability. This HOM-AMUW architecture is a promising scaffold to design the gas electrodes with ultrahigh rate performance not only for Li-O2 batteries but also for other metal-air batteries. Graphical abstract: